Judaizing and Identity in the Earliest Transylvanian Sabbatarian Writings (1588?–1621) - Réka Újlaki-Nagy (Wrocławski Przegląd Teologiczny)
The denominational and national identity of Transylvanian Sabbatarians (‘Judaizers’) has been constantly debated since the mid-19th century discovery of Sabbatarian literature. The question has always been haunted by mythologizing tendencies. The absence of something that was a given in the case of other denominations – that is, reflection on their native land and their nationality – was explained in terms of denominationally and nationally biased standpoints. Although most scholars had their own opinion about this question, no one has tried to perform a detailed inquiry into the problem, based on the texts themselves, and within a context of the Sabbatarians’ attitude to Jews. The present essay tries to address this problem. Utilizing a relevant set of keywords, I try to identify the signs of identity-creation in the earliest extant texts, and I also try to explore the Sabbatarian perception of Jews. My investigation reinforces the hypothesis that the absence of a patriotic voice is rooted in the theological advance towards Jews. Although the perception of the Jews is not entirely positive in Sabbatarian texts, their role is unique, making them essential for salvation. This indicates the later direction of the formation of Sabbatarian national and denominational identity, which is a gradual movement towards Jewishness, leading to ‘assimilation’ later.